A Numerical Approach to the Solution of the Supersonic Flow Field in the Exit Plane of High Turning Angle Turbine Blades - Sutradhar, Chandra Subhash (My University, 1982)
The power output from a high turning angle turbine blade passage depends on many factors and the most important of all is the appropriate pressure distribution along the pressure and suction surfaces of the blades. The operation of a fully choked passage requires the specification of the proper operating pressure ratio to avoid the formation of any compression waves after the geometric throat which would otherwise generate a total pressure loss for the system.
With the advancement of computational methods, the two-dimensional supersonic flow field existing after a choked passage is elaborately analysed to avoid the adverse effect of compression waves on the blade performance. For different pressure ratios the characteristic waves as well as the pressure distribution are presented which give a theoretical prediction for the presence of a possible shock wave after the geometric throat of the passage. The shock free operation of the passage definitely increases the power output of the cascade. The stream tube method of pressure distribution is extended for generating the characteristic waves covering the entire supersonic flow field existing near the trailing edge of the fully choked passage of a high turning angle turbine blade passage.
Keywords: Mechanical Engineering; Mechanical Engineering